2017
DOI: 10.1017/cem.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictive factors of return to the emergency department following an initial release by the emergency department for acute heart failure

Abstract: Many heart failure patients (i.e. 1 in 5 patients) are released from the ED and then suffer return to ED. Patients with multiple medical comorbidities, and those with abnormal initial vital signs are at increased risk for return to ED and should be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…ED visits for HF compose nearly 1% of all ED visits in the United States, carry high economic costs, and are associated with high rates of hospitalization and recidivism. 2729 A previous Kaiser Permanente Southern California and Northwest study found higher ED visit rates in HFpEF patients when compared with HFrEF and HFbEF patients. 7 However, this study did not identify HF-related ED visits, included a smaller cohort of patients followed only after an index HF hospitalization, and excluded HFbEF patients.…”
Section: Discussionmentioning
confidence: 98%
“…ED visits for HF compose nearly 1% of all ED visits in the United States, carry high economic costs, and are associated with high rates of hospitalization and recidivism. 2729 A previous Kaiser Permanente Southern California and Northwest study found higher ED visit rates in HFpEF patients when compared with HFrEF and HFbEF patients. 7 However, this study did not identify HF-related ED visits, included a smaller cohort of patients followed only after an index HF hospitalization, and excluded HFbEF patients.…”
Section: Discussionmentioning
confidence: 98%
“…The rate of return to emergency services by patients with heart failure was 20% in a Canadian study. 19 In another investigation, patients with this diagnosis and aged ≥80 years were significantly more prone to returning, when compared to younger individuals. 20 Still, in both studies, the use of antiarrhythmic medications was negatively associated with the occurrence of the outcome.…”
Section: Discussionmentioning
confidence: 92%
“…20 Still, in both studies, the use of antiarrhythmic medications was negatively associated with the occurrence of the outcome. 19 , 20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations